The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1006/viro.2002.1688
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Bovine Immunodeficiency Virus Packaging Signal and RRE and Incorporation into a Minimal Gene Transfer Vector

Abstract: Gene transfer systems based on lentiviruses have emerged as promising gene delivery vehicles for human gene therapy due to their ability to efficiently transduce nondividing target cells. Both primate and nonprimate lentiviruses have been used for construction of lentiviral vectors. An early generation of gene transfer system based on bovine immunodeficiency virus (BIV) has been developed (R. D. Berkowitz, H. Ilves, W. Y. Lin, K. Eckert, A. Coward, S. Tamaki, G. Veres, and I. Plavec, 2001, J. Virol. 75, 3371-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…A representative lambda library was constructed with salmon swim bladder sarcoma DNA partially digested with MboI and size selected on a 5 to 20% potassium acetate gradient; fragments of 15 to 20 kb were cloned and packaged using a lambda DASH II/BamHI vector kit (Stratagene, La Jolla, CA) using Gigapak II XL packaging extract according to the manufacturer's instructions. A library of 800,000 plaques was screened with a 143-bp pol sequence probe labeled with 32 P by random priming (Roche, Indianapolis, IN). Of the 150 positive clones obtained, twenty were plated and selected through two additional rounds of hybridization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A representative lambda library was constructed with salmon swim bladder sarcoma DNA partially digested with MboI and size selected on a 5 to 20% potassium acetate gradient; fragments of 15 to 20 kb were cloned and packaged using a lambda DASH II/BamHI vector kit (Stratagene, La Jolla, CA) using Gigapak II XL packaging extract according to the manufacturer's instructions. A library of 800,000 plaques was screened with a 143-bp pol sequence probe labeled with 32 P by random priming (Roche, Indianapolis, IN). Of the 150 positive clones obtained, twenty were plated and selected through two additional rounds of hybridization.…”
Section: Methodsmentioning
confidence: 99%
“…In human immunodeficiency virus type 1 (HIV-1) and other lentiviruses (28,32), utilization of the cPPT as an internal priming site during plusstrand synthesis has been demonstrated to generate a central DNA flap that enhances infection efficiency in nondividing cells (55). The proper displacement of the central DNA flap is dependent on adjacent central termination sequences (CTS) that terminate plus-strand synthesis initiated from the 3Ј LTR (6,26).…”
Section: Identification Of Sssvmentioning
confidence: 99%
“…The authors have further demonstrated that the 5 -distal 100 bp region S130 C. Delenda of gag sequences in conjunction with the 5 -UTR was sufficient for efficient RNA packaging [71]. In a similar way, the first 104 bp of BIV gag also contains a functional part of the packaging signal [27].…”
Section: Minimal Requirements For the Encapsidation Sitementioning
confidence: 91%
“…Associated with the central termination site (CTS) which dictates the reverse transcriptase (RT) ejection in the specific context of strand displacement synthesis, the cPPT cis-acting benefit for proviral nuclear facilitation has been clearly demonstrated in the HIV-1 [51,52], SIV [53], EIAV [54] and FIV [55] contexts. A putative cPPT/CTS element has also been maintained in BIV-derived vectors [27]. Therefore, the introduction of such autologous sequences into LV vector constructs has led to an increase in the percentage of transduced cells.…”
Section: Incorporation Of Additional Cis-acting Regulatory Sequencesmentioning
confidence: 99%
“…The other two primate lentiviruses, HIV-2 and SIV, have been developed as gene transfer vectors with limited success (D'Costa et al 2003;Gilbert and Wong-Staal 2001;Salani et al 2005). Nonprimate lentiviruses were also considered, such as FIV (Poeschla et al 1998;Saenz and Poeschla 2004), EIAV (Olsen 1998), BIV (Molina et al 2002), and CAEV (Mselli-Lakhal et al 2006). Among those nonprimate lentiviral vectors, FIV and EIAV were commonly used.…”
Section: Non-hiv-1 Derived Lentiviral Vectorsmentioning
confidence: 99%